Supervisão judicial do financiamento de campanha eleitoral: proteção de direitos individuais, maximização de bens democráticos e modelo antidominação - Marques Neto, Pedro (2018)
This research analyses and contrasts the arguments employed by the Brazilian and American constitutional courts on the constitutionality of campaign finance regulation. The judicialization of campaign finance disputes poses two issues: (i) first, to determine under which circumstances judicial intervention on the organization of electoral politics is legitimate; (ii) second, to lay down how constitutional courts should reason when - and how they have been reasoning about - they oversee the organization of democratic politics. These issues have at their core the relationship between constitutional jurisdiction and democratic politics in terms of the role displayed by the Judiciary in the (institutional) design of democracy. This research claims that constitutional courts can legitimately intervene in the organization of democracy in order to minimize democratic harms caused by institutional designs that promote domination in the electoral sphere, in accordance with the antidomination model of judicial oversight of democracy proposed by Yasmin Dawood. My argument is that constitutional courts should develop a structural conception of democratic rights focused on the minimization of democratic harms, in contrast with individual conception of such rights or structural conceptions focused on the maximization of democratic goods. Thus, I contrast the antidomination model with the concrete experience of the Brazilian and American constitutional courts. While the Supreme Court of the United States’ approach focuses on the protection of individual rights, I claim that the Supreme Federal Court of Brazil’s approach focuses on the maximization of democratic goods. I claim that both approaches distort the judicial oversight of campaign finance regulation by the Brazilian and the American constitutional courts and so I propose alternative answers based on the antidomination model, according to which courts are more deferential, though not submissive, to the political choices of the legislative body.